Cumulative effective dose from recurrent CT examinations in Europe: proposal for clinical guidance based on an ESR EuroSafe Imaging survey - Frija, Guy; Damilakis, John; Paulo, Graciano; Loose, Reinhard; Vano, Eliseo (European radiology, 2021)
In recent years, the issue of cumulative effective dose received from recurrent computed tomography examinations has become a subject of increasing concern internationally. Evidence, predominantly from the USA, has shown that a significant number of patients receive a cumulative effective dose of 100 mSv or greater. To obtain a European perspective, EuroSafe Imaging carried out a survey to collect European data on cumulative radiation exposure of patients from recurrent computed tomography examinations. The survey found that a relatively low percentage of patients (0.5%) received a cumulative effective dose equal to or higher than 100 mSv from computed tomography, most of them having an oncological disease. However, there is considerable variation between institutions as these values ranged from 0 to 2.72%, highlighting that local practice or, depending on the institution and its medical focus, local patient conditions are likely to be a significant factor in the levels of cumulative effective dose received, rather than this simply being a global phenomenon. This paper also provides some practical actions to support the management of cumulative effective dose and to refine or improve practice where recurrent examinations are required. These actions are focused around increasing awareness of referring physicians through encouraging local dialogue, actions focused on optimisation where a team approach is critical, better use of modern equipment and the use of Dose Management and Clinical Decision Support Systems together with focused clinical audits. The proper use of cumulative effective dose should be part of training programmes for referrers and practitioners, including what information to give to patients. Patient summary Radiation is used to the benefit of patients in diagnostic procedures such as CT examinations, and in therapeutic procedures like the external radiation treatment for cancer. However, radiation is also known to increase the risk of cancer. To oversee this risk, the cumulative effective dose (CED) received by a patient from imaging procedures over his or her life is important. In this paper, the authors, on behalf of EuroSafe Imaging, report on a survey carried out in Europe that aims to estimate the proportion of patients that undergo CT examinations and are exposed to a CED of more than 100 mSv. At the same time, the survey enquires about and underlines radiologists’ measures and radiology departments’ strategies to limit such exposure. Over the period of 2015–2018, respondents reported that 0.5% (0–2.72%) of patients were exposed to a CED of ≥ 100 mSv from imaging procedures. The background radiation dose in Europe depends on the location, but it is around 2.5 mSv per year. It is obvious that patients with cancer, chronic diseases and trauma run the highest risk of having a high CED. However, even if the number of patients exposed to ≥ 100 mSv is relatively low, it is important to lower this number even further. Measures could consist in using procedures that do not necessitate radiation, using very low dose procedures, being very critical in requiring imaging procedures and increasing awareness about the issue. Key Points • A relatively low percentage of patients (0.5%) received a cumulative effective dose from CT computed tomography equal to or greater than 100 mSv, in Europe, most of them having an oncological disease. • There is a wide range in the number of patients who receive cumulative effective dose equal to or greater than 100 mSv (0–2.72%) and optimisation should be improved. • Increasing the awareness of referring physicians through encouraging local dialogue, concrete actions focused on optimisation and development of dose management systems is suggested.